Expression of FOXJ1 in hepatocellular carcinoma: Correlation with patients' prognosis and tumor cell proliferation12. Issue 8 (4th April 2012) - Chen, Hong‐Wei; Huang, Xiao‐Dong; Li, Hong‐Chen; He, Song; Ni, Run‐Zhou; Chen, Cui‐Hua; Peng, Chen; Wu, Gang; Wang, Gui‐Hua; Wang, Ying‐Ying; Zhao, Yun‐Hong; Zhang, Yi‐Xin; et al.
Abstract FOXJ1 is a member of the forkhead box (FOX) family of transcription factors. Recent studies suggested that FOXJ1 may function as a tumor suppressor gene in breast cancer. To investigate the potential roles of FOXJ1 in hepatocellular carcinoma (HCC), expression of FOXJ1 was first examined in eight paired frozen HCC and adjacent noncancerous liver tissues by Western blot, and we found that FOXJ1 was upregulated in HCC specimens. In addition, immunohistochemistry was performed to confirm our results in 108 HCC samples. Moreover, we also evaluated its relation with clinicopathological variables and the prognostic significance. The data showed that high expression of FOXJ1 was associated with histological grade (P < 0.001), and FOXJ1 was positively correlated with proliferation marker Ki‐67 (P < 0.01). Univariate analysis suggested that FOXJ1 expression was associated with poor prognosis (P < 0.001). Multivariate analysis indicated that tumor grade (P < 0.0001), metastasis (P = 0.0451), tumor size (P = 0.0459), FOXJ1 (P = 0.0011), and Ki‐67 (P = 0.0006) were independent prognostic markers for HCC. Furthermore, we noted that there existed the change of the level of FOXJ1 subcellular localization during cell‐cycle transition in HepG2 cells by immunofluorescence and cell fractionation. Besides, we employed FOXJ1 overexpression/knockdown approaches to investigate the effects of FOXJ1 on HCC cell proliferation and cell‐cycle distribution and found that overexpression of FOXJ1 can promote tumor cell proliferation and cell‐cycle transition. Our results suggested that FOXJ1 was overexpressed in HCCs and associated with histological grade and poor prognosis. Overexpression of FOXJ1 was also involved in tumor cell proliferation and cell‐cycle progression in HCC cell lines. © 2012 Wiley Periodicals, Inc.